Implementation of Marketing Mix in Efforts to Increase Sales Volume at the Wildan Sandals Store - Fauziah, Syifa; Hadita, Hadita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to determine the implementation of the marketing mix strategy used through the 4P aspects including product, price, place and promotion with efforts to increase sales volume at the Wildan Sandal Store. This type of research uses descriptive qualitative. Data collection in this research uses primary data taken in direct observations and interviews with the business owner. The results obtained from this research are that the products marketed at the Wildan Sandal Shop have various models with different sizes ranging from children to adults. The conclusion resulting from this research is that implementing a good marketing mix strategy in business can have an influence on increasing the sales volume of the Wildan Sandal Store.